Interaction of Predatory Ladybird Beetle, Micraspis discolor with Nilaparvata lugens throughout Paddy Growing Seasons - Hanifah, Alia Natasha; Musa, Nadia Nisha; Noraziyah, Abd Aziz Shamsudin; Yaakop, Salmah (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2024)
Coccinellidae is a high-interest family that has performed well and is widely distributed. It is valuable in economic service because it acts as an agricultural biological control agent. The Micraspis discolor (Syn=Verania) (Coleoptera: Coccinellidae) is a successful omnivorous predator in rice ecosystem and functions well as a general biological control for maintaining the population of brown planthopper (BPH) (Nilaparvata lugens), the major rice pest worldwide. Studies of natural enemies’ abundance are necessary to increase the practical use of biological control in agriculture. This study investigated the abundance correlation of M. discolor (prey) and rice pest N. lugens (prey) from two different geographical areas of rice fields in west and south Peninsular Malaysia. The cyclone lightrap and sweep net method succeeded in collecting 185 individuals of M. discolor and N. lugens. The study indicated that M. discolor, and the N. lugens collected from Selangor were more numerous than Johor in the ripening phase than in the reproductive and vegetative phases. M. discolor can be found in all stages of rice growth. There are positive correlations between M. discolor and N. lugens in both localities throughout the rice growing season. The positive correlation highlighted that the number of pests has increased parallel to the number of predators and vice versa. The use of M. discolor as a predator is essential in agriculture, along with the treatment of a healthy ecosystem landscape of diverse vegetation combinations, which helps to reduce the use of pesticides.